Efficient light-trapping in ultrathin GaAs solar cells using quasi-random photonic crystals. (1st June 2022) - Buencuerpo, Jeronimo; Saenz, Theresa E.; Steger, Mark; Young, Michelle; Warren, Emily L.; Geisz, John F.; Steiner, Myles A.; Tamboli, Adele C.
Abstract: Ultrathin solar cells reduce material usage and allow the use of lower-quality materials thanks to their one order of magnitude smaller thickness than their conventional counterparts. However, efficient photonic light-trapping is required to harvest the incident light efficiently for an otherwise insufficient absorber thickness. Quasi-random photonic crystals are predicted to have high efficient light-trapping while being more robust under angle and thickness variations than simple photonic crystals. Here we experimentally demonstrate a light-trapping solution based on quasi-random photonic crystals fabricated by polymer blend lithography. We control the average lattice parameter by modifying the spin-coating speed. We demonstrate an ultrathin GaAs cell of 260 nm with a rear quasi-random pattern with submicron features, and a J sc = 26.4 mA/cm 2 and an efficiency of 22.35% under the global solar spectrum. Graphical abstract: Highlights: Low-cost fabrication of quasi-random photonic crystals using polymer blends. Facile tuning of the structure's reciprocal space by changing the spin speed. Ultrathin GaAs cell of 260 nm absorber with a best in class efficiency of 22.35%. High Voc (1.12 V) GaAs ultrathin cells with and without rear-pattern.